Shadow state structures and the threat to anti-corruption enforcement: evidence from Uzbekistan’s telecommunications bribery scandal - Lasslett, Kristian (Crime, law and social change, 2024)
The role which corporate and financial secrecy vehicles play in enabling transnational corruption has justifiably received growing scholarly and policy interest. Less attention, however, has been given to the enabling role played by political secrecy vehicles. Political secrecy vehicles denote arrangements that allow individuals to clandestinely exercise public authority, which is concealed by a formal bureaucratic façade. This article develops analytical categories for deconstructing political secrecy structures and pinpointing the threat they pose to anti-corruption enforcement. These structures and threats are then empirically explored through an investigative case study. The case study plots how shadow political space in Uzbekistan and the simulacra of impartial public administration, was utilised by a kleptocratic syndicate to conceal an international bribery scheme, and then weaponised by the conspirators to successfully frustrate enforcement efforts in Europe. Drawing on key lessons from the case study, proposals are made for how the threats posed by political secrecy structures can be jurisprudentially and practically counteracted.